LAYANAN BIMBINGAN DAN KONSELING ANAK PUTUS SEKOLAH DI KELURAHAN BUNGKUTOKO KECAMATAN NAMBO KOTA KENDARI - Sumarlin Sumarlin (Anoa : Jurnal Pengabdian Masyarakat Sosial, Politik, Budaya, Hukum, Ekonomi, 2022)
This Community Service Program is titled "Guidance and Counseling Services for School Dropouts in Bungkutoko Village, Nambo District, Kendari City, Southeast Sulawesi. In general, the purpose of this service activity is through training activities, the community is given knowledge so that they can optimize their willingness to continue their higher education and try to have skills so that they can work in companies in the village of Bungkutoka and even be able to create their own businesses that can support their needs their lives are more worthy and encourage community participation towards school dropouts so that they can implement the learning that has been obtained. The implementation method of this activity is in the form of a needs analysis method, which is a method or method to find out the difference between the desired/ought condition (should be/ought to be) or expected condition and the existing condition (what is), analysis through perspective analysis, FGD Method, and approach method and partner participation. The product produced in this community service activity is the formation of an understanding of the concept of the importance of education. Apart from these achievements, some external targets achieved through this activity include: scientific publication in journals; publication in electronic mass media (Sultra kini/Media online); method or system and accompanied by a dedicated team as a result of following this activity.